The heart of the humanities : reading, writing, teaching - Edmundson, Mark, 1952- (New York : Bloomsbury, 2018)
A renowned professor of English at the University of Virginia, Mark Edmundson has devoted his career to tough-minded yet optimistic advocacy for the humanities. He argues for the importance of reading and writing to an examined and fruitful life and affirms the invaluable role of teachers in opening up fresh paths for their students. In his series of books Why Read?, Why Teach?, and Why Write? Edmundson explored the vital worldly roles of reading, teaching, and writing, earning a vocal following of writers, teachers, and scholars at the top of their fields, from novelist Tom Perrotta to critics Laura Kipnis and J. Hillis Miller. Now for the first time The Heart of the Humanities collects into one volume this triad of impassioned arguments, including an introduction from the author on the value of education in the present and for the future. The perfect gift for students, recent graduates, writers, teachers, and anyone interested in education and the life of the mind, this omnibus edition will make a powerful and timely case for strengthening the humanities both in schools and in our society. --
Introduction -- Why read? -- Why write? -- Why teach?
Keywords: Humanities -- Study and teaching (Higher); Education, Higher -- Aims and objectives -- United States; Literature -- Study and teaching (Higher); Rhetoric -- Study and teaching (Higher); Education, Higher -- Aims and objectives; Humanities -- Study and teaching; Rhetoric -- Study and teaching; United States